2011
DOI: 10.1590/s0037-86822011000800012
|View full text |Cite
|
Sign up to set email alerts
|

Programa de Controle da Doença de Chagas no estado de São Paulo, Brasil: o controle e a vigilância da transmissão vetorial

Abstract: RESUMO ABSTRACTThe control of the vectors of Chagas' disease in the State of Sao Paulo are discussed, mainly those activities that led to the elimination of Triatoma infestans. Secondary factors that helped the control such as rural exodus are also analyzed. The article shows that since 1965 the control became a campaign with different phases due to the epidemiological situation, the acquired knowledge and the entomological surveillance. After 25 years of work, the elimination of all the focus of Triatoma infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 12 publications
0
13
0
2
Order By: Relevance
“…As respostas ao controle químico foram bastante diversas no caso do vetor introduzido (T. infestans) e de espécies nativas (Silveira & Máximo 1985). Enquanto para T. infestans a infestação foi sendo progressiva e consistentemente focalizada, as espécies autóctones mantinham sua dispersão inicial, mesmo que as populações fossem sendo reduzidas e as colônias intradomiciliares extintas.…”
Section: As Respostas Ao Controleunclassified
“…As respostas ao controle químico foram bastante diversas no caso do vetor introduzido (T. infestans) e de espécies nativas (Silveira & Máximo 1985). Enquanto para T. infestans a infestação foi sendo progressiva e consistentemente focalizada, as espécies autóctones mantinham sua dispersão inicial, mesmo que as populações fossem sendo reduzidas e as colônias intradomiciliares extintas.…”
Section: As Respostas Ao Controleunclassified
“…The presence of T. sordida and P. megistus in the State of São Paulo results from their ability to invade and colonize human habitations 4) . After the control of T. infestans infection, P. megistus stands out in epidemiological terms as an entomological indicator of home infestation, and studies on the density (5) (9) showed that, in the State of São Paulo, about 1% of the T. sordida and 9% of the P. megistus species tested positive for T. cruzi infection. According to Silva et al (10) , Panstrongylus megistus is an important vector for T. cruzi infection in the state, with high rates of natural transmission.…”
mentioning
confidence: 99%
“…Although there has been an increase in the number of insects captured, these triatomines were found to be negative for T. cruzi. Research by Silva et al (2011a) in São Paulo State showed that about 1% of T. sordida and 9% of P. megistus were positive for T. cruzi.…”
Section: Discussionmentioning
confidence: 99%